Hand Hygiene and Soap-Making Workshop at SMA Ricci 1, Jakarta - Sherly Tandi Arrang; Yohanes Eko Adi Prasetyanto; Regina Carissa; Angela Lovefrensia Lim; Charlie Angelia; Anna Lithania Kilmas; Gladys Monica Lehman; Natasha Lie; Bintang Salsa Billah Arthani; Agnes Melody; Verent Halim; Vanessa Gracia Santoso; Revista Noveria; Clarissa Tifani Harumi Pasaribu; Putriana Rachmawati (Amalee: Indonesian Journal of Community Research and Engagement, 2026)
Contaminated hands are a major route for the transmission of microorganisms and contribute to the spread of infectious diseases, particularly in school environments where close interpersonal contact facilitates transmission. Although awareness of hand hygiene is generally adequate, adolescents' consistent handwashing practices remain suboptimal. Because adolescence is a critical period for establishing lifelong health behaviors, school-based interventions provide an important opportunity to improve hand hygiene knowledge, awareness, and behavioral intention, thereby promoting sustained healthy practices and reducing the risk of communicable diseases. This program aimed to improve students’ knowledge of hand hygiene and to provide practical skills through a soap-making workshop at SMA Ricci 1 in Jakarta. The methods included health education via interactive lectures, pre- and post-tests, and a hands-on workshop, with 141 and 71 students attending the educational session and the workshop, respectively. The results showed an increase in the mean knowledge score from 75.25 to 85.60, with 55.32% to 88.65% of students in the “good” knowledge category. Additionally, over 90% of the participants gave high ratings for the workshop’s clarity, usefulness, and relevance. The program effectively improved students’ knowledge and awareness of hand hygiene while providing practical experience to support healthy hygiene behavior.